I want to poke my eyes out!: Why meetings are painful and tips on how to make them better - Coleman, Tara; Powell, Charissa (My University, 2021)
At one of the first meetings Tara Coleman attended as a new professional, Dove chocolate was distributed with the agenda to “sweeten the subject matter”. As the meeting progressed, she learned that the chocolate was a bribe to get people in the room, and a sign of tremendous boredom and irritation ahead. Soon she saw her colleagues turn the foil wrappers into little swords and stab themselves in the heart and eyes to show how their feelings on how the meeting was going. Spoiler alert, candy does not sweeten boring subject matter and foil swords are sharp enough to hurt the unguarded eyeball. You know the ones, you’re not sure why you are in the room, one person dominates the conversation, nothing is accomplished, and you might leave with a completely different understanding of what happened than someone else. You might have even wanted to fake an injury to get out of it early. Meetings can be exhausting and leave you feeling like you wasted valuable time. And since the pandemic, for some meetings have gone from painful to torture. All at once folks needed to learn Zoom, struggle with shared wifi, and have fewer reasons to get up and move around. While we can’t promise to make meetings a party, we can provide ways to make them less painful for everyone involved. If this proposal is selected, folks will receive tangible tips that will shape meeting expectations and roles, free or low cost tools that allow for voices to be heard that would otherwise be hidden or talked over, and sage advice about how to best use and respect everyone’s time.